Paradox of materialism: Exploring the complex relationship between consumption and well-being - Mutaz Maawia Osman (International Journal of Studies in Psychology)
Abstract—This study critically examines the complex relationship between consumption and well-being, emphasising the limitations of materialism and exploring alternative avenues for achieving lasting happiness. While material consumption may offer temporary satisfaction, it ultimately falls short of providing long-term well-being. Drawing from a wide range of empirical evidence and theoretical perspectives, this study argues that true and enduring happiness is more effectively attained through the pursuit of intrinsic values, meaningful relationships, and experiences and through sustainable and mindful consumption practices. Concepts such as hedonic adaptation and the broaden-and-build theory of positive emotions are discussed to explain why experiences and non-materialistic values contribute more significantly to sustained satisfaction. The study also delves into the societal implications of rampant consumerism and economic disparity, advocating for policy interventions prioritising human well-being over economic growth. Through a comprehensive analysis, the study offers insights into fostering a more fulfilling and sustainable approach to living, both on an individual and societal level.